NOTAS SOBRE LAS ADAPTACIONES DE MENECMOS DE PLAUTO EN LAS TRADUCCIONES ESPAÑOLAS DEL SIGLO XVI - Ruiz-Funes Torres, María; Morales Ortiz, Alicia (Myrtia, 1996)
The aim of this article is to analyse the anonymous translation of Plauto’s ’Menecmos’, attributed to Juan Verzosa (Antwerp 1555), as well as the translation of the same work carried out by Juan de Timoneda (Valencia 1559). Here, we pay particular attention to the procedures of adaptation used by the translator in terms of their different purposes. This study leads us to conclude that the differences which exist between both versions should be attributed to the translator’s intention in each of them. That is, the anonymous translation is intended to be read whereas Timoneda aims at a version to be performed.